2011
DOI: 10.1590/s0100-29452011000200013
|View full text |Cite
|
Sign up to set email alerts
|

Extrato de alho e óleo vegetal no controle do míldio da videira

Abstract: RESUMO -O objetivo deste trabalho foi verificar o efeito do extrato de alho e do óleo vegetal no controle do míldio da videira cv. Isabel (Vitis labrusca). A severidade da doença, expressa pela área abaixo da curva de progresso da doença (AACPD), e a germinação de esporângios de seu agente causal Plasmopara viticola foram as variáveis avaliadas. Os tratamentos consistiram em 0; 5; 10; 15; 20; 25 ou 30 mL L -1 de extrato de alho adicionados de 2,5 mL L -1 óleo vegetal, calda bordalesa (1:1:100) e testemunha (se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
5
0
3
Order By: Relevance
“…The authors attributed this higher fungistatic activity to the loss of the antifungal properties of the extracts, due to the longer incubation period. Leite et al (2011) also reported fungistatic activity of garlic extract and vegetable oil in the control of grapevine downy mildew and germination of sporangia of P. viticola causative agent.…”
Section: Effect Of Volatile Compounds Of Essential Oils On the Spore mentioning
confidence: 95%
See 1 more Smart Citation
“…The authors attributed this higher fungistatic activity to the loss of the antifungal properties of the extracts, due to the longer incubation period. Leite et al (2011) also reported fungistatic activity of garlic extract and vegetable oil in the control of grapevine downy mildew and germination of sporangia of P. viticola causative agent.…”
Section: Effect Of Volatile Compounds Of Essential Oils On the Spore mentioning
confidence: 95%
“…In the worldwide literature, there is a significant increase in the number of studies that seek to find antifungal activity of essential oils as an alternative control of several plant pathogens, with promising results for cinnamon (RANASINGHE et al, 2002;KISHORE et al, 2007;MAQBOOL et al, 2010), eucalyptus (LORENZETTI et al, 2012), marjoram (FIALHO, 2012), melaleuca (FRASSON et al,2010), peppermint (CHAGAS et al, 2014) oregano (MALLET et al, 2014) and white thyme oils (PERINA et al, 2015). Aiming at to contribute to one more option to control the downy mildew of the grapevine, the objective of this study was to evaluate the antifungal effect of essential oils on the spore germination of P. viticola, a causal agent of grapevine downy mildew.…”
Section: Introductionmentioning
confidence: 99%
“…Na videira, o óleo vegetal associado ao extrato de alho (Allium sativum) afetou negativamente a germinação de P. viticola e a severidade do míldio em condições de campo (Leite et al, 2011). Este óleo associado ao extrato aquoso de cinamomo (Melia azedarach) controlou outra importante doença da videira denominada de antracnose da videira (Silva et al, 2012b).…”
Section: Discussionunclassified
“…Silva et al (2012a) observaram que em condições de campo (videiras da casta 'Isabel'), a aplicação isolada do óleo vegetal na dose de 2,5 mL L-1 proporcionou uma redução de 76,3% na AACED do míldio em relação à testemunha absoluta (somente água), enquanto que em outro ensaio, verificou-se que o óleo vegetal proporcionou uma redução de 64,0% na AACED para a antracnose da videira (Silva et al, 2012b). Leite et al (2011) verificaram que o óleo vegetal na dose de 2,5 mL L -1 reduziu em 52% a AACED do míldio da videira em relação ao tratamento testemunha. Em outros patossistemas, o óleo vegetal de sementes de Brassicaceae destacou-se no controle do oídio do melão, quando comparado com fungicidas convencionais, como pentaconazole, miclobutanil, azoxystrobin e enxofre (Candido et al, 2014).…”
Section: Efeito Do óLeo Vegetal No Controle Do Míldio Na Casta 'Isabeunclassified
“…For vine leaf diseases, garlic extract provided control of Plasmopara viticola [4] Phomopsis viticola and Elsinoe ampelina [5,6]. The garlic extract was also effective in controlling in vitro Botryosphaeria dothidea, Diplodia a e-mail: carine.rusin@gmail.com seriata andEutypa lata, Macrodidyma Ilyonectri and Phaeocremonium aleophilum [7].…”
Section: Introductionmentioning
confidence: 99%